Analysis of long-term follow-up and examination of pathological liver tissue in chronic hepatitis E. Issue 6 (June 2016) - Liu, Li; Liu, Yunhua; Du, Yingrong; Liu, Chunyun; Li, Weikun; Li, Huimin; Jia, Ting; Chang, Lixian
Abstract: Hepatitis E is chronic in immunocompromised patients with HIV infection, organ transplant, or radiation and chemotherapy. General cases are not chronic. Fifty-five cases were collected and followed up for 4–14 years. It was found that chronic hepatitis E is more common in males, but a high degree of inflammatory activity and fibrosis was not evident. After 4–14 years of follow-up observation, cirrhosis or liver cancer did not appear. This is significantly different from the hepatitis B and C viruses. We speculated that the chronic mechanism in the general patients with hepatitis E might be different from that of immunocompromised cases.